Controller Design For DFIG Driven By Variable Speed Wind Turbine Using Static Output Feedback Technique - Bharti, O. P.; Saket, R. K.; Nagar, S. K. (Engineering, Technology & Applied Science Research, 2016)
This paper describes the controller design for a DFIG based wind energy generation system using the static output feedback technique through the LMI Toolbox. The features of the DFIG, its converters and their controllers are discussed. The lower order nominal representation of DFIG is obtained using numerical differentiation of the SIMULINK model which is subsequently used for PID controller design. The obtained results are compared with existing methods for performance enhancement of the DFIG and wind energy conversion systems.